Features of organotopic remodeling of bone tissue and implanted osteoplastic material in Charcot neuro/osteoarthropathy - Stanislav A. Osnach; Victor G. Protsko; Vasily V. Kuznetsov; Vladimir N. Obolensky; Sargon K. Tamoev; Yulia V. Khamidullina; Dmitry Yu. Borzunov (Гений oртопедии, 2023)
Introduction Despite the recognition of MRI as the gold diagnostic standard for Charcot arthropathy, there is evidence in the literature that MSCT is more informative for objective qualitative and quantitative diagnosis of the condition, primarily of the bone skeleton of the Charcot foot, in comparison with standard radiography. The sensitivity and specificity of these methods are different. Purpose To reveal the features of organotopic remodeling of bone tissue and implanted osteoplastic material in the course of midfoot and hindfoot subtotal defects management in Charcot neuro-osteoarthropathy. Materials and methods The analysis of bone tissue and implanted osteoplastic material density was carried out in a case series that included 11 patients with Charcot neuro-osteoarthropathy who underwent a two‑stage procedure for bone defects in the hindfoot and midfoot with the Ilizarov apparatus. We studied CT and MRI scans and measured bone regenerate density before treatment, at the stages of transosseous osteosynthesis, and 3, 6, and 12 months after surgery. Results In all patients, varying increase in the amount and volume of bone tissue was visualized due to intensive periosteal bone formation along with the formation of bone ankylosis in the joints along combined with a consistent increase in the optical density of bone regenerates. The formation of the new bone tissue ran without the signs of lysis or sequestration. The conducted studies indicate that the sizes and architectonics of bone fragments are more differentiated in CT than in MRI scans. Discussion It is known that the bone, despite its high mineralization, continuously rebuilds, restores and adapts itself to certain functional conditions. This constant dynamic process of adaptive remodeling depends mostly on optimal blood supply, metabolic activity and the coordinated work of bone cell elements. The data obtained show angiogenesis in the compromised tissues in patients with Charcot foot and consistent remodeling of the graft into the new bone tissue. Conclusion The allobone in the composition of the combined bone graft does not reduce the likelihood of complete remodeling of the newly formed bone tissue. Higher bone density by filling in a bone defect with a graft differs from distraction regenerate that initially has low bone density. CT and MRI are highly effective and informative diagnostic methods for surgical treatment. In reconstructive interventions in the patients with Charcot foot under the conditions of transosseous osteosynthesis, preference among radiological study methods should be given to CT.